Teaching Translation in Israel High Schools - Kozminsky, Ely; Weizman, Elda; Horowitz, Hannah (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThe paper describes the English Language Translation Program (LTP), as it is implemented in Israeli high schools. It further discusses the results of an empirical study designed to evaluate the students' achievements following the program. The LTP is a two-year option for the 11th and 12th grades. In a two-hour weekly course they practice written translation from English (L2) into Hebrew (L1), and discuss textually relevant translation problems with the aim of increasing language awareness and developing language competence. Evaluation of the program at the end of 1994 indicated that the LTP students improved the metalanguage skills related to translation, and also gained 5 extra percentage points in the regular English matriculation exams at the end of grade 12, compared to the non-LTP controls. Administrative, pedagogical, and conceptual problems in implementing the program are discussed.